The Influence of Corporate Governance and Corporate Strategy on Financial Reporting Tone and Readability: Evidence from the Iraqi Stock Exchange (2015-2024) - Idan, Hayder; Kadhim, Sarah Mijbel; Wahhab, Asaad M. A. (Journal of International Accounting, Taxation and Information Systems, 2026)
This study investigates the determinants of clarity, readability, and user comprehension of financial reports, with particular emphasis on the roles of corporate governance mechanisms and business strategies among industrial companies listed on the Iraq Stock Exchange (ISE). A statistical sample of 20 out of 24 listed industrial companies was examined over the period 2015-2024, and multiple regression analysis was employed to test the formulated research hypotheses. The findings demonstrate that both corporate governance components and business strategies exert a direct, statistically significant influence on the linguistic characteristics of financial reports, particularly tone and readability. Regarding tone, independent company ownership, board independence, audit committee independence, and the adoption of an aggressive business strategy were found to have a positive effect, whereas management involvement, family ownership, and a defensive business strategy exerted a negative influence. With respect to readability, board independence, audit committee independence, the frequency of audit committee meetings, and an aggressive strategy, these factors had a direct, positive impact, while management involvement, family ownership, and a defensive strategy had a negative effect. The explained variance ratios further indicate that corporate governance components account for approximately 62.7% of the variance in financial report tone, whereas business strategy accounts for approximately 74.3% of the variance in readability. These results underscore the critical importance of robust governance structures and proactive strategic orientations in enhancing the transparency and communicative quality of corporate financial disclosures.